Desain Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Pesantren Pada Madrasah Aliyah Pancasila Bengkulu - Matondang, Mutiara (JPT : Jurnal Pendidikan Tematik, 2024)
This research resulted in a number of findings, namely: (1) The education curriculum of Madrasah Aliyah Pancasila Bengkulu City is designed based on the curriculum of the Ministry of Religious Affairs combined with the curriculum of Islamic boarding schools and inspired by the curriculum of modern Islamic boarding schools and salafiyah Islamic boarding schools in general. (2) The implementation of the Islamic Religious Education curriculum at Madrasah Aliyah Pancasila Bengkulu City is carried out in line with the curriculum design it developed, namely the combination of madrasah and Islamic boarding school learning.